The distribution of Coronal Plane Alignment of the Knee (CPAK) phenotypes in the Malaysian population and their correlation with demographic variables - Wai Kit Wong; Azliana Abu Bakar Sajak; Hwa Sen Chua (Arthroplasty)
Abstract Background Only 80% of patients are satisfied with their outcomes post-TKA. Mounting attention has been paid to constitutional limb alignment and individualized alignment strategies in recent years. MacDessi et al. proposed the CPAK classification, which takes into account the patients’ arithmetic hip-knee-ankle axis (aHKA) and joint line obliquity (JLO). In this study, we aimed to establish local demographic data, compare them with published data, and assess their correlations with modifiable variables. Methods A total of 500 end-stage osteoarthritic knees subjected to TKA were radiologically analyzed. The lateral distal femoral angle (LDFA) and medial proximal tibial angle (MPTA) were calculated from long limb radiographs before the aHKA and JLO were derived and a CPAK phenotype was assigned. Demographic data were harvested and analyzed for possible correlations. Results There were 160 males (32%) and 340 females (68%), with a mean age of 66.42 years (range, 47–88). The mean MPTA was 85.8° (± 3.0)°, and the mean LDFA was 87.6° (± 2.4)°. The average aHKA was a varus of 1.8° (± 4.2)°, and the average JLO was 173.4° (± 3.45)°. The most common CPAK phenotype was Type 1 (43.4%). The Intraclass Correlation Coefficient demonstrated excellent reliability (> 0.9). No correlation existed between CPAK phenotypes and age, height, weight, or body mass index (BMI), but CPAK phenotype was significantly correlated with gender. Conclusion An urban Malaysian population with osteoarthritic knees was found to be constitutionally varus, with the most common phenotype being varus aHKA with an apex-distal JLO. Constitutional alignment is not influenced by factors such as age, height, weight, or BMI. Level of Evidence Retrospective Observational Study-III.